Pancasila Is An Element Of Consciousness That Is Produced And Integral In The Social Practices Of Indonesia Society - J. Agung Indratmoko, Risa Shoffia (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
but ideology has an active role in shaping the social structure itself, it can be likened to a map that provides structure and human understanding in understanding in the scope, especially the surrounding social situation. The study of ideology is the same as the study of law, this is because the formation of law always involves ideology as the basic element and of course comes from the deposits of social behavior that exist in society. Pancasila is an ideology that describes fundamental characters that are in harmony with the social life of the Indonesian people. The type of research I use in this research is Legal Research. The approach used in this research is a historical approach. There are problems that occur in the current era, that the application of Pancasila in the digital era has many various things that are vulnerable to division and hostility even though the easier information can be accessed. With the strengthening of Pancasila values as the basis of national awareness, all existing problems can be overcome and can be implemented properly by improving digital literacy, reviving the spirit of mutual cooperation, strengthening education about ethics and morals, especially in the digital world, using social media wisely, participating in a smart role to maintain the truth of information circulating and uphold the values of Pancasila in life of the nation and state.